Shrub encroachment is linked to extirpation of an apex predator. (5th December 2016) - Gordon, Christopher E.; Eldridge, David J.; Ripple, William J.; Crowther, Mathew S.; Moore, Ben D.; Letnic, Mike
Abstract: The abundance of shrubs has increased throughout Earth's arid lands. This 'shrub encroachment' has been linked to livestock grazing, fire‐suppression and elevated atmospheric CO2 concentrations facilitating shrub recruitment. Apex predators initiate trophic cascades which can influence the abundance of many species across multiple trophic levels within ecosystems. Extirpation of apex predators is linked inextricably to pastoralism, but has not been considered as a factor contributing to shrub encroachment. Here, we ask if trophic cascades triggered by the extirpation of Australia's largest terrestrial predator, the dingo ( Canis dingo ), could be a driver of shrub encroachment in the Strzelecki Desert, Australia. We use aerial photographs spanning a 51‐year period to compare shrub cover between areas where dingoes are historically rare and common. We then quantify contemporary patterns of shrub, shrub seedling and mammal abundances, and use structural equation modelling to compare competing trophic cascade hypotheses to explain how dingoes could influence shrub recruitment. Finally, we track the fate of seedlings of an encroaching shrub, hopbush ( Dodonaea viscosa angustissima ), during a period optimal for seedling recruitment, and quantify removal rates of hopbush seeds by rodents from enriched seed patches. Shrub cover was 26–48% greater in areas where dingoes were rare than common. Our structural equation modelling supported the hypothesis that dingo removal facilitates shrub encroachment by triggering a four level trophic cascade. According to this model, increased mesopredator abundance in the absence of dingoes results in suppressed abundance of consumers of shrub seeds and seedlings, rodents and rabbits respectively. In turn, suppressed abundances of rodents and rabbits in the absence of dingoes relaxed a recruitment bottleneck for shrubs. The results of our SEM were supported by results showing that rates of hopbush seedling survival and seed removal were 1·7 times greater and 2·1 times lower in areas where dingoes were rare than common. Our study provides evidence linking the suppression of an apex predator to the historic encroachment of shrubs. We contend that trophic cascades induced by apex predator extirpation may be an overlooked driver of shrub encroachment. Abstract : Shrub cover has increased throughout Earth's rangelands. The authors propose a novel model accounting for this 'shrub encroachment': trophic cascades induced by apex predator extirpation facilitate shrub recruitment and success. GIS tools, field data and statistical techniques are used to test this model in arid Australia.